Hybrid Hydrogel Supplemented with Algal Polysaccharide for Potential Use in Biomedical Applications - Dana Stan; Andreea-Cristina Mirica; Sorin Mocanu; Diana Stan; Iunia Podolean; Natalia Candu; Magdi El Fergani; Laura Mihaela Stefan; Ana-Maria Seciu-Grama; Ludmila Aricov; Oana Brincoveanu; Carmen Moldovan; et al. (Gels)
Hydrogels are a viable option for biomedical applications due to their biocompatibility, biodegradability, and ability to incorporate various healing agents while maintaining their biological efficacy. This study focused on the preparation and characterization of novel hybrid hydrogels enriched with the natural algae compound Ulvan for potential use in wound dressings. The characterization of the hydrogel membranes involved multiple methods to assess their structural, mechanical, and chemical properties, such as pH measurements, swelling, moisture content and uptake, gel fraction, hydrolytic degradation, protein adsorption and denaturation tests, rheological measurements, SEM, biocompatibility testing, and scratch wound assay. The hydrogel obtained with a higher concentration of Ulvan (1 mg/mL) exhibited superior mechanical properties, a swelling index of 264%, a water content of 55%, and a lower degradation percentage. In terms of rheological properties, the inclusion of ULV in the hydrogel composition enhanced gel strength, and the Alginate + PVA + 1.0ULV sample demonstrated the greatest resistance to deformation. All hydrogels exhibited good biocompatibility, with cell viability above 70% and no obvious morphological modifications. The addition of Ulvan potentiates the regenerative effect of hydrogel membranes. Subsequent studies will focus on encapsulating bioactive compounds, investigating their release behavior, and evaluating their active biological effects.